Continuous vs. discontinuous drinking of an ethanol liquid diet in peripubertal rats : effect on 24-hour variation of lymph node and splenic mitogenic responses and lymphocyte subset populations - Jiménez Ortega, Vanesa (2011)
Fil: Jiménez Ortega, Vanesa. Universidad Complutense. Facultad de Medicina. Departamento de Bioquímica y Biología Molecular III; España